Exploring the professionalisation of sports coaching from the athlete`s point of view: a study of professional players from Sweden - Schubring, A.; Lundvall, S.; Rylander, P. (Sport in Society: Cultures, Commerce, Media, Politics, 2024)
The professionalisation of sports coaching is approached in different ways depending on the country. In Sweden, social welfare ideals and traditions of volunteering have allowed coaching to be less professionalised. The aim of this article is to explore the impact of the professionalisation of sports coaching from the athlete`s perspective. Interviews with six top-level Swedish players in women`s and men`s team sports were analysed using Bourdieu`s theory of social fields. We found that the players` experiences with coaching reflect the doxa, power relations and capitals of their specific fields. Professionalisation was found to have multi-facetted effects on players and their careers. The environments of semi-professionalised Swedish clubs appear to benefit youth and holistic player development, however limited resources encourage players to migrate. Top professionalised clubs boost player performance and career development but run the risk of commodification and abuse. In conclusion, sport organisations are advised to keep local practices and athletes` perspectives in mind when navigating the global push towards the professionalisation of sport.